Nano-particle silver powder and preparation method thereof

Nanosilver powder is prepared by liquid phase chemical reduction method, which solves the problems of uneven particle size distribution and high ablation rate in the prior art, and achieves nanosilver powder with low fever loss, high stability and good conductivity, meeting the needs of heterojunction battery process.

CN119910177APending Publication Date: 2025-05-02NANTONG LIANSHENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510358305.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, nano silver powder has uneven particle size distribution, high ablation rate, and poor stability of industrial production batches after mass production, which cannot meet the high requirements of heterojunction battery technology for low-temperature slurries.

Method used

Using liquid phase chemical reduction method, silver ammonia solution is used as the silver source, hydrazine hydrate or formaldehyde as the reducing agent. Under the protection of the dispersant, nanoparticle silver powder with a particle size of 100-300 nm is prepared by precisely controlling the reaction conditions.

Benefits of technology

The obtained nano silver powder has low burn loss, good batch stability, large single batch yield, meets industrial needs, and maintains good conductivity under low temperature processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910177A_ABST
    Figure CN119910177A_ABST
Patent Text Reader

Abstract

The invention provides nano-particle silver powder and a preparation method thereof, and belongs to the technical field of silver powder preparation. The preparation method comprises the following steps: dissolving silver nitrate in normal-temperature deionized water to form a silver nitrate solution, sequentially adding ammonia water and lauric acid into the silver nitrate solution, and stirring for dissolving to obtain an oxidation solution; hydrazine hydrate is dissolved in normal-temperature deionized water, and a reduction solution is obtained; and adding a dispersing agent solution into a reaction container, adding the reducing solution into the dispersing agent solution at the temperature of 15-20 DEG C, then rapidly adding the oxidation solution into the reaction container through a flow controller, and carrying out stirring, sedimentation cleaning, alcohol soaking, suction filtration, drying, crushing, primary screening, crushing and secondary screening to obtain the nano-particle silver powder with the particle size of 100-300 nm. According to the method, the nano silver powder is prepared through liquid phase chemical reduction, the reaction process can be accurately controlled, the batch stability of the obtained product is good, the single-batch yield is large, and the industrial requirement can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silver powder preparation, and in particular relates to nano-particle silver powder and a preparation method thereof. Background Art

[0002] The current photovoltaic technology landscape has undergone significant changes compared to the past era dominated by a single technology. TOPCon technology has rapidly developed into the mainstream solar cell technology. Although the market size of technologies such as heterojunction (HJT) and back contact (XBC) is relatively small, they have also achieved large-scale mass production with the support of tens of gigawatts. At present, the comprehensive cost of HJT cells is higher than that of TOPCon, so researchers are trying to help the terminal solve the industry's difficult problems by reducing the cost of metallization without losing efficiency and reliability. In order to control costs, HJT battery manufacturers try to use narrower stencil openings, finer grid lines, and faster printing / ink return speeds. In order to meet the high market demand for such solutions, the printing window of silver-coated copper paste needs to be updated and iterated to adapt to the narrow opening of 14um screen, the narrow opening of 10um steel mesh, and the needs of high-speed printing. This requires that the metal materials such as silver-coated copper powder and nano-silver powder in the silver-coated copper paste have good dispersibility and sintering activity.

[0003] The heterojunction battery process needs to be carried out below 200°C, so the slurry used for heterojunction is different from the high-temperature silver paste used for other crystalline silicon batteries. It uses low-temperature slurry. Heterojunction slurry is generally composed of conductive fillers and organic polymers. Conductive fillers are generally nano-silver powder, silver-coated copper powder, nano-copper powder, etc., which mainly play the role of conducting electrons and determine the electrical properties of heterojunction slurry. Among the current preparation methods for silver powder, most are only in the experimental stage, with small single batch output, and the particle size distribution, ablation, tap density and other data of the products after mass production vary greatly. The stability of industrial production batches is poor. Generally, the nano-silver powder is agglomerated after drying and has a high ablation (usually greater than 1%), which cannot meet the needs well. At the same time, other components remaining in the electrode under low-temperature process lead to high resistivity and deviation in conductivity. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provide a nano-particle silver powder and a preparation method thereof.

[0005] In one aspect of the present disclosure, a method for preparing nanoparticle silver powder is provided.

[0006] The preparation method comprises:

[0007] Dissolving silver nitrate in deionized water at room temperature to form a silver nitrate solution, adding ammonia water and lauric acid to the silver nitrate solution in sequence, stirring and dissolving, and obtaining an oxidizing solution;

[0008] forming a reducing solution;

[0009] A dispersant solution is added to a reaction container, the reducing solution is added to the dispersant solution at 15-20° C., and the oxidizing solution is quickly added to the reaction container through a flow controller, and the nanoparticle silver powder with a particle size of 100-300 nm is obtained through stirring, sedimentation cleaning, alcohol soaking, suction filtration, drying, crushing, primary screening, pulverization, and secondary screening.

[0010] Optionally, the ratio of the added amount of the silver nitrate to the added amount of the lauric acid is 10:(1-3).

[0011] Optionally, the ratio of the added amount of the silver nitrate to the added amount of the lauric acid is 10:(1.5-2).

[0012] Optionally, forming a reducing solution comprises:

[0013] Dissolve hydrazine hydrate or formaldehyde in deionized water at room temperature to obtain a reducing solution.

[0014] Optionally, the mass ratio of the hydrazine hydrate or formaldehyde to deionized water at room temperature is 7:(20-30).

[0015] Optionally, the mass ratio of the hydrazine hydrate or formaldehyde to deionized water at room temperature is 7:(20-25).

[0016] Optionally, the dispersant is PVP.

[0017] Optionally, the dispersant is added in an amount of 40-70% by weight of the silver nitrate.

[0018] Optionally, the stirring speed in the reaction vessel is 300-500 r / min.

[0019] Optionally, the nanoparticle silver powder has a D50 particle size of 0.2-0.3 μm, a D100 of less than 1 μm, and a tap density of 4.0 g / cm 3 Above, the specific surface area is 4m 2 / g or more, and the burning loss is within 0.7%.

[0020] Another aspect of the present disclosure provides a nano-particle silver powder, which is prepared by the preparation method described above.

[0021] The present disclosure proposes a nano-particle silver powder and a preparation method thereof. The preparation method comprises: dissolving silver nitrate in deionized water at room temperature to form a silver nitrate solution, adding ammonia water and lauric acid to the silver nitrate solution in sequence, stirring and dissolving to obtain an oxidizing solution; dissolving hydrazine hydrate in deionized water at room temperature to obtain a reducing solution; adding a dispersant solution to a reaction container, adding the reducing solution to the dispersant solution at 15-20°C, and then quickly adding the oxidizing solution to the reaction container through a flow controller, stirring, settling and cleaning, alcohol soaking, suction filtration, drying, crushing, primary screening, pulverizing, and secondary screening to obtain a nano-particle silver powder with a particle size of 100-300nm. The present disclosure prepares nano-silver powder by liquid phase chemical reduction, using silver ammonia solution as a silver source, hydrazine hydrate or formaldehyde as a reducing agent, and under the protection of one or more dispersants, accurately controlling the reaction conditions to obtain a spherical silver powder with a particle size of 100-300 nanometers. The obtained product has low burn loss, good batch stability, and a large single batch output, which can meet industrialization needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a flowchart of a method for preparing nano-particle silver powder according to a specific embodiment of the present disclosure;

[0023] Figure 2 is a morphology diagram of the nanoparticle silver powder of Example 1 of the present disclosure;

[0024] Figure 3 This is a morphology picture of the nanoparticle silver powder of Example 2 of the present disclosure. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0026] like Figure 1 As shown, in one aspect of the present disclosure, a method for preparing nano-particle silver powder is provided S100, which specifically includes the following steps S110 to S130:

[0027] S110, dissolving silver nitrate in deionized water at room temperature to form a silver nitrate solution, adding ammonia water and lauric acid to the silver nitrate solution in sequence, stirring and dissolving, and obtaining an oxidizing solution.

[0028] Specifically, analytical pure silver nitrate is dissolved in deionized water at room temperature, 25% ammonia water is added, stirred to clarify, lauric acid is added, stirred to dissolve, and an oxidizing solution is obtained, and the temperature of the oxidizing solution is controlled at 15-20°C.

[0029] In some preferred embodiments, the ratio of silver nitrate to lauric acid is 10:(1-3), more preferably, the ratio of silver nitrate to lauric acid is 10:(1.5-2), for example, 10:1.5, 10:2, etc. Of course, in other embodiments, the ratio of silver nitrate to lauric acid can also be 10:1, 10:2.5, 10:3, etc. Controlling the amount of lauric acid can help to obtain lower burn loss.

[0030] In the present embodiment, by adding lauric acid in the step of preparing the oxidation solution, lauric acid and silver ammonium ion are reacted, the balance of silver ion nucleation and growth rate is controlled, and the reaction rate can be controlled better. When the lauric acid dosage is less, the reaction speed is too fast, and the growth rate is greater than the nucleation rate, and the nano silver particles grow up and reunite. When the lauric acid dosage is more, the reaction speed is slower, and the nucleation rate is suitable for the growth rate, so the particle size of the nano silver powder is smaller and evenly distributed. That is to say, the lauric acid of the present embodiment acts on the silver ammonium ion, and an amount of lauric acid can balance the speed of nano silver ion nucleation and growth, and obtains a small particle size and evenly distributed silver powder.

[0031] In other preferred embodiments, the content ratio of silver nitrate to ammonia water is 10:(8-9). For example, when the amount of silver nitrate is 100 parts by mass, the amount of ammonia water may be preferably 80 parts by mass, 85 parts by mass, 90 parts by mass, etc.

[0032] S120. Dissolve hydrazine hydrate or formaldehyde in deionized water at room temperature to obtain a reducing solution.

[0033] In some preferred embodiments, the mass ratio of hydrazine hydrate or formaldehyde to deionized water at room temperature is 7:(20-30). More preferably, the mass ratio of hydrazine hydrate or formaldehyde to deionized water at room temperature is preferably 7:(20-25), for example, 7:20, 7:22, 7:24, 7:25, etc. Of course, in other embodiments, the content of the two can also be other ratios such as 7:30. By controlling the content of other reducing agents such as hydrazine hydrate or formaldehyde and deionized water within the above range, it helps to control the reaction rate of reducing silver ions to elemental silver.

[0034] It should be noted that, since the reaction temperature of the present embodiment is room temperature, some reducing agents with weak reducing properties, such as glucose, are difficult to reduce silver at room temperature. Some reducing agents, even if they can reduce nano silver, react slowly due to low reaction temperature, making it difficult for silver particles to form nuclei and grow, and are prone to agglomeration. Therefore, in general, the reducing agent of the present embodiment is preferably hydrazine hydrate or formaldehyde, which has strong reducing ability and can effectively reduce silver at room temperature to ensure the smooth progress of the reaction.

[0035] Similarly, the temperature of the reducing liquid obtained in step S120 can be controlled at 15-20°C.

[0036] S130, adding a dispersant solution into a reaction container, adding a reducing solution into the dispersant solution at 15-20°C, and then quickly adding an oxidizing solution into the reaction container through a flow controller, and obtaining nano-particle silver powder with a particle size of 100-300 nm through stirring, sedimentation cleaning, alcohol soaking, suction filtration, drying, crushing, primary screening, pulverization, and secondary screening.

[0037] Specifically, add a certain amount of deionized water to the reactor, start stirring, add a certain amount of dispersant to form a dispersant solution, start temperature control, and control the solution temperature at 15-20°C; after the temperature stabilizes, add the reducing solution to the dispersant solution; then quickly add the oxidizing solution to the reactor through a flow controller, and continue stirring for 10 minutes after adding; then settle and wash until the conductivity of the supernatant is below 10μs / cm, then add a large amount of alcohol to soak, filter, dry, crush with a swing crusher, sieve, crush with a high-speed crusher, and then sieve to obtain the finished powder. Sedimentation cleaning and alcohol soaking can help to obtain lower burn loss.

[0038] It should be noted that the oxidizing liquid can be quickly added to the mixed liquid consisting of the reducing liquid and the dispersant through air compression, and each batch is completed within 5 seconds in total. This allows the oxidizing liquid to quickly and fully contact with the reducing liquid and the dispersant, making the concentration of reactants in various parts of the reaction system more consistent, avoiding local excessive or insufficient reaction, and helping to generate silver powder with uniform particle size distribution. At the same time, the rapid addition of the oxidizing liquid can trigger the reaction in a short time, shorten the reaction time, and improve production efficiency.

[0039] In some preferred embodiments, the amount of dispersant added is 40-70% of the weight of silver nitrate, and the dispersant can be polyvinyl alcohol, polyacrylic acid, PVP, etc., preferably PVP (K90). The dispersant in the above content can help the silver powder to disperse well without affecting the nucleation and growth of the silver powder, ensuring that the silver ions can be smoothly reduced to silver element, and does not interfere with the normal reaction rate, which is conducive to forming silver powder with a more uniform particle size distribution. Controlling the amount of dispersant can help to obtain lower burnout.

[0040] In other preferred embodiments, the stirring speed in the reaction container is 300-500 r / min, which can control the reaction speed of reducing silver ions to silver element and improve the quality of silver powder.

[0041] It should be understood that in the process of synthesizing nano silver powder, if the reaction is completed in an instant, nano silver powder with large and uneven particle size will be obtained, and the morphology of the nano silver powder is also different. In view of this, the present invention adds lauric acid as a modifier in the oxidizing solution, and the long chain of lauric acid has a strong adsorption effect on silver ammonium ions, or lauric acid forms a lauric acid silver ammonium complex when lauric acid encounters silver ammonium ions. This adsorption or the formed complex reduces the reactivity of silver ions, which helps to form nano silver powder with small particle size and uniform distribution.

[0042] The present invention adopts a liquid phase chemical reduction method, with silver ammonia solution as the silver source, hydrazine hydrate or formaldehyde as the reducing agent, and lauric acid is added to the oxidation solution, and under the protection of one or more dispersants, by accurately controlling the reaction conditions, a spherical silver powder with a particle size of 100-300nm can be obtained. The above reaction process can be accurately controlled, the obtained product has low burnout, good batch stability, and a large single batch output, which effectively solves the problems of product agglomeration and ablation, and while ensuring good conductivity, the printing performance is better, which can meet the needs of industrialization.

[0043] Another aspect of the present disclosure provides a nano silver powder, which is prepared by the preparation method described above. Please refer to the above description for the specific preparation method, which will not be described in detail here.

[0044] In some preferred embodiments, the nano silver powder prepared by the above process has a D50 particle size of 0.2-0.3 μm, a D100 of less than 1 μm, and a tap density of 4.0 g / cm 3 Above, the specific surface area is 4m 2 / g or more, and the burning loss is within 0.7%.

[0045] The nano silver powder obtained in the present invention has a dark gray-black appearance, a high specific surface area, and a low sintering temperature while ensuring the necessary fluidity of the powder. It can be used as a good low-temperature sintering silver powder in HJT slurry.

[0046] The preparation method of nano-particle silver powder will be further described below in conjunction with specific examples:

[0047] Example 1

[0048] (1) Weigh 2000 g of analytical pure silver nitrate and put it into a preparation kettle 1, add 8 kg of room temperature deionized water, start stirring, and add 1800 g of ammonia water after dissolution and clarification. After stirring and clarification, add 200 g of electronic grade lauric acid. After stirring and dissolution is complete, adjust the solution temperature to 15° C. and keep warm.

[0049] (2) Weigh 150 g of analytical pure hydrazine hydrate and add it to preparation kettle 2. Add 450 g of deionized water at room temperature, stir for 5 minutes, then stop stirring and start keeping warm to 15°C.

[0050] (3) Add 10L of deionized water and 1200g of PVP (K value 31) to the reactor, start stirring, wait until the dispersant is thoroughly dissolved and the temperature is controlled at 15°C, add the reducing solution, and then quickly add the oxidizing solution. Set the stirring speed to 400r / min and continue stirring for 10 minutes after adding.

[0051] (4) Wash by sedimentation until the conductivity of the supernatant is less than 10 μs / cm, transfer to a solid-liquid separator for filtration, filter until there is no moisture on the surface, add 200 L of alcohol and soak for 1 hour, filter again, dry, use a swing crusher for preliminary crushing through an 80-mesh sieve, and then use a high-speed powder mill to process through a 500-mesh sieve to obtain the finished powder.

[0052] According to Table 1 and Figure 2 It can be seen that the silver powder obtained from different batches has a relatively concentrated particle size distribution, a large specific surface area, and low burnout. Among them, the D10 of the silver powder is 0.15-0.18μm, the D50 is 0.24-0.29μm, the D90 is 0.59-0.63μm, the D100 is 0.92-0.96μm, and the specific surface area is 4.11-4.13m 2 / g, tap density is 5.10-5.12g / cm 3 , the burn-in loss at 538°C is 0.5%.

[0053] Furthermore, the silver powder obtained in batch 1 of this embodiment 1 was mixed with an acrylic organic carrier and a pine alcohol solvent in the same mass ratio of 86:7:7 to form a low-temperature silver paste; the low-temperature silver paste was printed on a heterojunction silicon wafer by screen printing using the same printing process, and heated to 160°C for 5 minutes to form a silver electrode. The line resistivity of the silver electrode was tested. As shown in Table 1, the line resistivity was 3.59×10 -6 Ω·cm.

[0054] Example 2

[0055] (1) Weigh 2000 g of analytical pure silver nitrate and put it into a preparation kettle 1, add 8 kg of room temperature deionized water, start stirring, add 1800 g of ammonia water after dissolution and clarification, stir and clarify, add 300 g of electronic grade lauric acid, stir and dissolve completely, adjust the solution temperature to 20° C., and keep warm.

[0056] (2) Weigh 160 g of analytical pure hydrazine hydrate and add it to preparation kettle 2. Add 500 g of deionized water at room temperature, stir for 5 minutes, then stop stirring and start keeping warm to 20°C.

[0057] (3) Add 10L of deionized water and 1000g of PVP (K value 90) to the reactor, start stirring, wait until the dispersant is thoroughly dissolved and the temperature is controlled at 15°C, add the reducing solution, and then quickly add the oxidizing solution. Set the stirring speed to 500r / min and continue stirring for 10 minutes after adding.

[0058] (4) Wash by sedimentation until the conductivity of the supernatant is less than 10 μs / cm, transfer to a solid-liquid separator for filtration, filter until there is no moisture on the surface, add 200 L of alcohol and soak for 1 hour, filter again, dry, use a swing crusher for preliminary crushing through an 80-mesh sieve, and then use a high-speed powder mill to process through a 500-mesh sieve to obtain the finished powder.

[0059] According to Table 1 and Figure 3 It can be seen that the silver powder obtained from different batches has a relatively concentrated particle size distribution, a large specific surface area, and low burnout. Among them, the D10 of the silver powder is 0.11-0.12μm, the D50 is 0.23-0.26μm, the D90 is 0.58-0.63μm, the D100 is 0.85-0.90μm, and the specific surface area is 4.78-4.82m 2 / g, tap density is 4.53-4.60g / cm 3 , the burning loss at 538°C is 0.62%.

[0060] Furthermore, the silver powder obtained in batch 1 of this embodiment 2 was mixed with an acrylic organic carrier and a pine alcohol solvent in the same mass ratio of 86:7:7 to form a low-temperature silver paste; the low-temperature silver paste was printed on a heterojunction silicon wafer by screen printing using the same printing process, and heated to 160°C for 5 minutes to form a silver electrode. The line resistivity of the silver electrode was tested. As shown in Table 1, the line resistivity was 3.52×10 -6 Ω·cm.

[0061] Comparative Example 1

[0062] (1) Weigh 2000 g of analytical pure silver nitrate and put it into a preparation kettle 1, add 8.2 kg of room temperature deionized water, start stirring, and add 1800 g of ammonia water after dissolving and clarifying. After stirring and clarifying, adjust the solution temperature to 15° C. after stirring and dissolving completely, and keep warm.

[0063] (2) Weigh 150 g of analytical pure hydrazine hydrate and add it to preparation kettle 2. Add 450 g of deionized water at room temperature, stir for 5 minutes, then stop stirring and start keeping warm to 15°C.

[0064] (3) Add 10L of deionized water and 1200g of PVP (K value 31) to the reactor, start stirring, wait until the dispersant is thoroughly dissolved and the temperature is controlled at 15 degrees, add the reducing solution, and then quickly add the oxidizing solution. Set the stirring speed to 400r / min and continue stirring for 10 minutes after adding.

[0065] (4) Wash by sedimentation until the conductivity of the supernatant is less than 10 μs / cm, transfer to a solid-liquid separator for filtration, filter until there is no moisture on the surface, add 200 L of alcohol and soak for 1 hour, filter again, dry, use a swing crusher for preliminary crushing through an 80-mesh sieve, and then use a high-speed powder mill to process through a 500-mesh sieve to obtain the finished powder.

[0066] According to Table 1, the particle size distribution of silver powder obtained from different batches is relatively dispersed and varies greatly. Among them, the D10 of silver powder is 0.30-0.62μm, D50 is 2.08-2.36μm, D90 is 2.46-2.85μm, D100 is 5.12-5.87μm, and the specific surface area is 3.52-3.76m 2 / g, tap density is 3.20-3.23g / cm 3 , the burning loss at 538°C is 0.53-0.54%.

[0067] Furthermore, the silver powder obtained in batch 1 of comparative example 1 was mixed with an acrylic organic carrier and a pine alcohol solvent in the same mass ratio of 86:7:7 to form a low-temperature silver paste; the low-temperature silver paste was printed on a heterojunction silicon wafer by screen printing using the same printing process, and heated to 160°C for 5 minutes to form a silver electrode. The line resistivity of the silver electrode was tested. As shown in Table 1, the line resistivity was 4.85×10 -6 Ω·cm.

[0068] Comparative Example 2

[0069] This comparative example uses commercially available silver powder, the D50 of which is the same as that of Example 2, but the burn loss is greater than 1%, and the line resistivity of the prepared slurry is also greater than that of Example 2.

[0070] Furthermore, the silver powder purchased in Comparative Example 2 was mixed with an acrylic organic carrier and a pine alcohol solvent in the same mass ratio of 86:7:7 to form a low-temperature silver paste; the low-temperature silver paste was printed on a heterojunction silicon wafer by screen printing using the same printing process, and heated to 160°C for 5 minutes to form a silver electrode. The line resistivity of the silver electrode was tested. As shown in Table 1, the line resistivity was 4.01×10 -6 Ω·cm.

[0071] Table 1 Test results of various embodiments and comparative examples

[0072]

[0073] In summary, by comparing the above Examples 1-2 with Comparative Example 1, it can be seen that by controlling the content of lauric acid and PVP, it is beneficial to reduce the particle size of the silver powder, increase the specific surface area and tap density, and improve the stability of different production batches, and the line resistivity of the obtained nanoparticle silver powder is low. By comparing the above Examples 1-2 with Comparative Example 2, it can be seen that when commercially available silver powder with a particle size close to that of the silver powder prepared in Examples 1 and 2 is used, its burn loss and line resistivity are both high.

[0074] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for preparing nanoparticle silver powder, characterized in that: The preparation method comprises: Dissolving silver nitrate in deionized water at room temperature to form a silver nitrate solution, adding ammonia water and lauric acid to the silver nitrate solution in sequence, stirring and dissolving, and obtaining an oxidizing solution; forming a reducing solution; A dispersant solution is added to a reaction container, the reducing solution is added to the dispersant solution at 15-20° C., and the oxidizing solution is quickly added to the reaction container through a flow controller, and the nanoparticle silver powder with a particle size of 100-300 nm is obtained through stirring, sedimentation cleaning, alcohol soaking, suction filtration, drying, crushing, primary screening, pulverization, and secondary screening.

2. The preparation method according to claim 1, characterized in that: The added amount ratio of the silver nitrate to the lauric acid is 10:(1-3).

3. The preparation method according to claim 2, characterized in that: The added amount ratio of the silver nitrate to the lauric acid is 10:(1.5-2).

4. The preparation method according to claim 1, characterized in that: A reducing solution is formed, comprising: Dissolve hydrazine hydrate or formaldehyde in deionized water at room temperature to obtain a reducing solution.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the hydrazine hydrate or formaldehyde to deionized water at room temperature is 7:(20-30).

6. The preparation method according to claim 1, characterized in that: The dispersant is PVP.

7. The preparation method according to claim 1, characterized in that: The added amount of the dispersant is 40-70% of the content of silver nitrate.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The stirring speed in the reaction vessel is 300-500 r / min.

9. The preparation method according to any one of claims 1 to 7, characterized in that: The nano-particle silver powder has a D50 particle size of 0.2-0.3 μm, a D100 of less than 1 μm, and a tap density of 4.0 g / cm 3 Above, the specific surface area is 4m 2 / g or more, and the burning loss is within 0.7%.

10. A nanoparticle silver powder, characterized in that: The nanoparticle silver powder is prepared by the preparation method according to any one of claims 1 to 9.